The survival of B cells is compromised in kidney disease - Doureradjou Peroumal; Chetan V. Jawale; Wonseok Choi; Hossein Rahimi; Danielle Antos; De-dong Li; Shuxia Wang; Godhev K. Manakkat Vijay; Isha Mehta; Raymond West; Muthusamy Thangaraju; Thomas D. Nolin; et al. (Nature Communications)
Abstract Antibody-mediated protection against pathogens is crucial to a healthy life. However, the recent SARS-CoV-2 pandemic has shown that pre-existing comorbid conditions including kidney disease account for compromised humoral immunity to infections. Individuals with kidney disease are not only susceptible to infections but also exhibit poor vaccine-induced antibody response. Using multiple mouse models of kidney disease, we demonstrate that renal dysfunction inhibits germinal center (GC) response against T-dependent antigens. GC B cells exhibit increased apoptosis in kidney disease. Uremic toxin hippuric acid drives loss of mitochondrial membrane potential, leading to increased apoptosis of GC B cells in a G-protein–coupled receptor 109A dependent manner. Finally, GC B cells and antibody titer are diminished in mice with kidney disease following influenza virus infection, a major cause of mortality in individuals with renal disorders. These results provide a mechanistic understanding of how renal dysfunction suppresses humoral immunity in patients with kidney disease.